Quality Assurance System of Pesantren As Branding In The Era Society 5.0 Era - Siti Aimah; Muhammad Nasih (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
This research aims to find a model of pesantren quality assurance system that impacts improving branding in the era of society 5.0. The research method used is a qualitative approach with a case study type with an interactive analysis of three models. The research results show that in the era of society 5.0, pesantren as educational institutions require branding using a quality assurance system like non-pesantren educational institutions because the current academic competition does not only rely on the unique characteristics that characterize pesantren but also builds a quality assurance system so that quality targets are achieved. According to or exceeding national education standards, it can be measured, as is done by the Pesantren Darussalam Blokagung Banyuwangi, which is a model for Islamic educational institutions that focus on improving quality as innovation and capital to compete at national and international levels.